1991
DOI: 10.1111/j.1365-2621.1991.tb05355.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximate, Nutritional and Microbiological Analyses of Milk‐Sweet Potato Mixtures Fermented with Yogurt Bacteria

Abstract: Milk, sweet potato (SP), sucrose and gelatin mixtures were fermented with yogurt bacteria. SP comprised 14, 16 or 18% of the milk-SP mixture. As SP increased, the following components decreased (dry weight basis, except for moisture): moisture, 81.3-79.7%; fat, 8.5-4.9%; and calculated calories, 1,726-1,651 kJ/lOOg (412-396 GalI 1OOg). Likewise, these components increased: nitrogen-free extract, 66.3-69.8% and vitamins C, 0.30 -0.41 mg/lOO g and A, 971-1,252 retinol equivalents/lOOg. On average, the product co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…With increased levels of SP concentration, it appears that there was a gradual decrease in LA content. However, Collins et al. (1991a,b) reported that percentage of TA decreased with increased levels of SP, sugars and fermentation time in the case of preparation of SP yoghurt.…”
Section: Resultsmentioning
confidence: 96%
“…With increased levels of SP concentration, it appears that there was a gradual decrease in LA content. However, Collins et al. (1991a,b) reported that percentage of TA decreased with increased levels of SP, sugars and fermentation time in the case of preparation of SP yoghurt.…”
Section: Resultsmentioning
confidence: 96%
“…A yogurt like product, having a titratable acidity of 0.85%, was prepared from sweet potato puree, milk, sucrose and freeze-dried yogurt inoculums (Collins et al, 1991a). On average, the product contained 19% protein, 3.8% ash, 2.5% dietary fibers, 80% moisture and 8.0-1.9% fat (Collins et al, 1991b). A trained panel gave a mean score of 7.7 (scale 1-10) for flavor, 3.9 (scale 1-5) for body/ texture and 3.8 for appearance and color (scale 1-5).…”
Section: Sweet Potato Curd and Yogurtmentioning
confidence: 99%